Nine-degree of Freedom Modeling and Flight Dynamic Analysis of Parafoil Aerial Delivery System. (2015) - Gang, Yu
Abstract: Because of its good aerodynamic performance and excellent controllability, the PADS which using the parachute like a wing has been widely used. To reach the accurate delivery target, the flight dynamic performance of PADS is very important. It is the foundation of the aerial delivery system's controllability and stability analysis. In this paper, we analyse the PADS' flight dynamic performance by simplifiedthe system at9-DOFand numerical modeling based on it. The system flight dynamic performance at the station of one side edge deflection and both side edge deflection have been compared. The results indicate that this paper's modeling and dynamic analysis way is viable.